2012
DOI: 10.1188/12.onf.603-608
|View full text |Cite
|
Sign up to set email alerts
|

Purposeful Interaction: Ways Latino Men Communicate About Prostate Cancer

Abstract: Purpose/Objectives To develop a descriptive framework of the communication processes used by Latinos with prostate cancer to communicate about their diagnosis. Research Approach A constructivist grounded theory approach was used to analyze and build a descriptive framework from semistructured interviews. Setting A university-affiliated urban hospital in southern California. Participants 30 Latinos treated for prostate cancer, who had at least one first-degree male relative (FDMR), and who lived near the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Our study extends previous work on familial communication about risk and the importance of culture (Ola Bratt, Emanuelsson, & Grönberg, 2003; Christophe, Vennin, Corbeil, Adenis, & Reich, 2009; Harris et al, 2010; Lagos et al, 2008; Palmquist et al, 2010; Shaw, Scott, & Ferrante, 2013; Vadaparampil, McIntyre, & Quinn, 2010; Wakefield et al, 2008). It follows up on our work with men with PCa about their disclosure patterns and communication with unaffected FDMRs (Maliski et al, 2012). Finally, there is a dearth of research specific to Latinos and prostate cancer despite the disparities observed in screening and stage at diagnosis which needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study extends previous work on familial communication about risk and the importance of culture (Ola Bratt, Emanuelsson, & Grönberg, 2003; Christophe, Vennin, Corbeil, Adenis, & Reich, 2009; Harris et al, 2010; Lagos et al, 2008; Palmquist et al, 2010; Shaw, Scott, & Ferrante, 2013; Vadaparampil, McIntyre, & Quinn, 2010; Wakefield et al, 2008). It follows up on our work with men with PCa about their disclosure patterns and communication with unaffected FDMRs (Maliski et al, 2012). Finally, there is a dearth of research specific to Latinos and prostate cancer despite the disparities observed in screening and stage at diagnosis which needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Maliski et al (2012) found that men affected by PCa with FDMRs hoped to communicate the importance of early detection to their FDMRs, but were highly selective about the depth of information disclosed, even to their adult children. They also stated they appreciated “respectful silence” from their relatives because they considered PCa an intimate issue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations